Verbal descriptions modulate flavour perception and evaluation of wine: An exploratory study using Riesling and Muscat Bailey A wines - Takuya Onuma (OENO One, 2024)
Significant efforts have been made in the wine industry to assist customers in making purchase decisions and enhance their drinking experience by providing verbal descriptions of the complex sensory characteristics of wine. However, the influence of such verbal descriptions on wine flavour perception and evaluation has not been examined. To fill this gap, this exploratory study performed an experiment using white Riesling wine from the 2021 German vintage and red Muscat Bailey A (MBA) wine from the 2019 Japanese vintage. Forty-six Japanese individuals (23 social drinkers and 23 wine experts) participated and were presented with two glasses of Riesling wine and two glasses of MBA wine with different verbal descriptions. One glass of Riesling/MBA wine was served with a description including its distinct aroma descriptor (i.e., a ‘petrol’ note for the Riesling wine and a ‘strawberry candy’ note for the MBA wine). For the other glass, the description did not include the descriptor. The participants were asked to taste the wines and rate their palatability, perceived sweetness intensities, acidity, astringency, alcohol sensation, body, and expensiveness on a 7-point scale. The results demonstrated that the social drinkers rated the Riesling wine with the ‘petrol’ descriptor as heavier-bodied and more expensive compared to the same wine without the descriptor. The wine experts were not as influenced as the social drinkers, but the experts rated the Riesling wine with the ‘petrol’ descriptor as less expensive. In the case of MBA wine with the ‘strawberry candy’ descriptor, the social drinkers rated it as more expensive, whereas the wine experts rated it as more palatable than the same wine without the descriptor. The results indicated that verbal descriptions of wine aroma indeed modulated the flavour perception and evaluation of wine, but the modulation effect varied between social drinkers and wine experts.